Efek Paparan Tepung Kedelai dan Tepung Tempe sebagai Sumber Fitoestrogen terhadap Jumlah Kelenjar Endometrium Uterus Mencit (Mus musculus L.) - Sitasiwi, Agung Janika (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Phytoestrogen has been known have many advantages in human health. It has estrogenic effect because it similarity in structure with natural estrogen. It action done by interact with estrogen receptor and inhibit the interaction of natural estrogen. The aim of this research was to evaluate the effect of soybean starch as phytoestrogen resources on reproduction of M. musculus, by the endometrial thickness and the sum ofendometrial glands aspects. The adult female Swiss Webster mice were used as animal treatment. The mice were treated with 0,975 mg/kg BW/day of soybean starch and 0,148g/kgBW/day. Uterine samples collected from every estrous phase made as histological slides with paraffin methods and stained with H.E.with 6 Î¼ in thickness. Anova with factorial design at 5% significances were used to analyzed the data. This search showed that there was no significances between control and treatment group so it can be concluded that the result were caused by the act of endogen estrogen in animal treatment.